1995
DOI: 10.1016/s1078-5884(05)80113-3
|View full text |Cite
|
Sign up to set email alerts
|

Screening for abdominal aortic aneurysms and associated risk factors in a general population

Abstract: Ultrasound screening for AAA is a reliable and useful method and should be focused on men, regardless of concurrent disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
69
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(77 citation statements)
references
References 18 publications
7
69
1
Order By: Relevance
“…Most clinical practice guidelines contain recommendations in favor of one -time AAA screening for men 65 -75 years old with a history of smoking using ultrasonographic scans (Ferket et al, 2011). However, this recommendation is poorly followed up in this target population, partly due to a lack of patients' compliance with an acceptance rate around 65% (Boll et al, 1998;Collin et al, 1988;Lederle et al, 1997;Lindholt et al, 1997;Simoni et al, 1995). Moreover, a recent study estimates that about half the patients with AAA were not eligible for screening under current guidelines and would have been missed (Kent et al, 2010).…”
Section: Aaa Screeningmentioning
confidence: 99%
“…Most clinical practice guidelines contain recommendations in favor of one -time AAA screening for men 65 -75 years old with a history of smoking using ultrasonographic scans (Ferket et al, 2011). However, this recommendation is poorly followed up in this target population, partly due to a lack of patients' compliance with an acceptance rate around 65% (Boll et al, 1998;Collin et al, 1988;Lederle et al, 1997;Lindholt et al, 1997;Simoni et al, 1995). Moreover, a recent study estimates that about half the patients with AAA were not eligible for screening under current guidelines and would have been missed (Kent et al, 2010).…”
Section: Aaa Screeningmentioning
confidence: 99%
“…Although it has been suggested that moderate alcohol consumption slows atherosclerosis by beneficial effects on lipid metabolism, thrombogenesis and fibrinolytic activity, the relation between alcohol consumption and a lower risk for CHD appears to be more complex 2,3) ; alcohol induces hypertension and is a risk factor for anuerysmal degeneration. As for the effect of alcohol consumption on aortic stiffness or decreased aortic compliance, evidence linking alcohol consumption and aortic stiffness is very few.…”
mentioning
confidence: 99%
“…Simoni et al [17] similarly reported increased prevalence of alcohol use in patients with AAA compared to patients with normal aortic diameter (41% vs. 65%, p<0.001) in their population screening study of 1,601 patients in Genoa, Italy. However, only univariable analysis was employed, without correction for multiple testing.…”
Section: Resultsmentioning
confidence: 88%
“…The search strategy identified 8 papers for inclusion in the systematic review [8,[16][17][18][19][20][21][22]. No randomised evidence or review articles were identified.…”
Section: Resultsmentioning
confidence: 99%